2021
DOI: 10.3390/md19110598
|View full text |Cite
|
Sign up to set email alerts
|

Functional Feeds to Tackle Meagre (Argyrosomus regius) Stress: Physiological Responses under Acute Stressful Handling Conditions

Abstract: Marine algae are recognised sources of bioactive compounds that have attracted great interest as nutritional supplements for aquaculture fish. Intensive rearing conditions often expose fish to husbandry-related stressors, rendering fish more susceptible to disease and reducing production yields. The present work evaluated the potential of two marine algae extracts (Fucus vesiculosus and Nannochloropsis gaditana) as nutritional supplements to mitigate stress effects in meagre (Argyrosomus regius) exposed to an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 75 publications
1
6
2
Order By: Relevance
“…Similarly, glucose levels increased after the stress test, especially in fish fed 0.5% tryptophan, potentially associated with heightened energy resources catabolism. In the primary stress response, cortisol release triggers a secondary response, leading to increased glucose levels and its transport to energy-demanding tissues for restoration [5,35,36]. This is consistent with the results obtained for the treatment with lower tryptophan content and coincident with those reported by Saavedra et al [24] for meagre, Abdel-Tawwab [35] for Nile tilapia and Hoseini et al [37] for sturgeon.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, glucose levels increased after the stress test, especially in fish fed 0.5% tryptophan, potentially associated with heightened energy resources catabolism. In the primary stress response, cortisol release triggers a secondary response, leading to increased glucose levels and its transport to energy-demanding tissues for restoration [5,35,36]. This is consistent with the results obtained for the treatment with lower tryptophan content and coincident with those reported by Saavedra et al [24] for meagre, Abdel-Tawwab [35] for Nile tilapia and Hoseini et al [37] for sturgeon.…”
Section: Discussionsupporting
confidence: 90%
“…The blood pH is decreased at the same time, because the accumulation of carbon dioxide increases the acidity of the blood [ 40 ]. Under hypoxic condition, the production of lactate is increased as an energy substrate for anaerobic respiration [ 41 , 42 ], which was the case in this study and short-horned sculpin ( Myoxocephalus scorpius ) [ 43 ]. It has been previously discovered that the increase in lactate level goes back to normal at 4 h post-anesthetic exposure in bonefish ( Albula vulpes ) and Atlantic salmon [ 41 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…65,92 Recently, the ability of the genus Nannochloropsis to reduce the effects of different types of stress related to aquaculture has been explored. On the one hand, Monteiro et al 93 showed that Tackle Meagre (Argyrosomus regius) supplemented with N. gaditana at 1% and subjected to acute handling stress had lower gene expression of proinflammatory cytokines tnf-α and il-1β genes, as well as a lower number of parameters related to oxidative stress. On the other hand, Abdelghany et al 66 found that the dietary administration of Nannochloropsis oculata at 10% and 15% to Nile tilapia (O. niloticus) subjected to air stress and then challenged with Aeromonas veronii induced greater protection compared with control fish.…”
Section: Nannochloropsis Gaditanamentioning
confidence: 99%